PENGELOLAAN RISIKO RANTAI PASOK SAYURAN ORGANIK (STUDI KASUS: PT. X, CISARUA, KABUPATEN BOGOR, JAWA BARAT) [Organic Vegetables Supply Chain Risk Management (Case Study: PT. X, Cisarua, District of Bogor, West Java)] - Kamal, Muhammad Arif; Djatna, Taufik; Sukardi, Sukardi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2019)
Achievement of the efficiency of the supply chain of organic vegetables PT. X needs to consider output in the form of added value and profit margins obtained from the input of delivery, fulfillment of requests, and risks faced by each actor. The purpose of this study was the management of supply chains of organic vegetables from farmers, entrepreneurs, retailers, and consumers in Cisarua, Bogor Regency, West Java. Based on the results of the analysis of value added by Hayami's method, it was known that retailers' profit margins tend to be bigger, but the contribution of value added is lower than that of farmers and companies. The results of risk measurement showed that the biggest risk index was in farmers due to the large risk of supply shortages. Measurement of efficiency using DEA showed that retailer actors were more efficient but tend to avoid risk. Achieving high efficiency at retailers indicated the ability to balance risk and revenue so that the delivery of organic vegetables in the supply chain was more efficient. Through a risk management mechanism with risk balancing and cost incentives because of the risk showed an increase in supply chain efficiency. This efficiency can be seen from the increase in the number of retailers 'demand and a decrease in supply / shipping inefficiency of farmers and companies in meeting retailers' demands.